Identification of chromosome breaks mediated by stress-induced apoptosis in nasopharyngeal carcinoma (NPC) - Tan, Sang Nee (Universiti Malaysia Sarawak (UNIMAS), 2012)
hromOSOmal rearrangements such as additions and deletions are genomIc instability frequently observed in nasopharyngeal carcinoma (NPC). However, the molecular mechanism underlying the NPC chromosomal rearrangements remains elusive. Recently, there is increasing evidence that the apoptotic nuclease caspase-activated deoxyribonuclease (CAD) is one of the players leading to translocation process in leukaemia. In normal cells, CAD exists as a complex with inhibitor of CAD (ICAD). ICAD possesses two caspase-3 deavage sites which are cleaved by caspase-3 when the apoptotic inducer is present. This releases the CAD from ICAD and allows it to degrade the chromosomal DNA. Although apoptosis is a cell death process, cells have the potential to survive apoptosis upon DNA repair) In human cells, chromosomal double-strand breaks (DSB) are primarily repaired by multiple repair pathways including non-homologous end joining (NHEJ) system. Non-homologous end joining pathway joins two cleaved DNA ends with microhomology, thus potentially resulting in erroneous DNA repair. Eventually, the surviving cells may carry chromosomal rearrangements. Apoptosis can be triggered by oxidative stress which occurs when the reactive oxygen species (ROS) generation exceeds the antioxidant defence capability. Oxidative DNA damage is strongly associated with carcinogenesis. It has recently become apparent that DNA breaks do not randomly distribute throughout a gene but usually cluster in certain regions containing specific chromatin structures. Matrix attachment region/scaffold attachment region (MARJSAR) is a binding site of DNA loop structure to nuclear scaffold proteins. It has DNA unwinding property which makes it to be a region of DNA fragility. This study hypothesised that stress-induced apoptosis may cause DNA breaks at MARJSAR and subsequently contribute to NPC chromosomal rearrangements in cells that survive apoptosis upon DNA repair. This study focused on the AF9 gene at 9p22 and the ABL gene at 9q34 because they are involved in translocations in leukaemia and are located at NPC common deletion sites. We aimed to identify DNA breaks mediated by stress-induced apoptosis, to relate the breakpoints to MARJSAR sites and to investigate the role of CAD in DNA cleavage mediated by stress-induced apoptosis. Upon hydrogen peroxide (H202) treatment, apoptotic evidence was observed in NPC and normal nasopharyngeal epithelial cells by flow cytometry. Numerous DNA breaks were detected in H202-treated NPC and normal nasopharyngeal epithelial cells by nested Inverse Polymerase Chain Reaction (IPCR). All breakpoints were mapped within close proximity to the MARJSAR sites. Besides, translocations were identified in H202-treated normal nasopharyngeal epithelial cells. Regions of microhomology were found at the translocation junctions. Furthermore, pre-treatment of caspase inhibitor which indirectly inhibits CAD significantly reduced the DNA breaks in H202-cotreated NPC and nonnal nasopharyngeal epithelial cells. In addition, a comparison of SAR and non-SAR regions showed that there were more chromosomal breaks detected within the non-SAR region which is occupied by nearly 60% of repeat elements. However, these breaks are not H202 dependent. This result shows that repeat elements might play an important role in inducing spontaneous chromosomal breaks, but not in chromosomal cleavage mediated by stress-induced apoptosis. Taken together, these findings suggested that under oxidative stress, surviving apoptosis involving compromised DNA repair could be one of the mechanisms contributing to NPC carcinogenesis. Matrix attachment region/scaffold attachment region located at the base of chromosomal loop structure could be the preferential sites of chromosomal cleavage. The apoptotic nuclease CAD may play an important role in DNA cleavage mediated by oxidative stress-induced apoptosis. Therefore, a potential model for oxidative stress-induced chromosomal rearrangements in NPC is proposed.